2022
DOI: 10.1021/acs.jpcb.1c09710
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Effects on the Menshutkin Reaction

Abstract: The Menshutkin reaction is a methyl transfer reaction relevant in fields ranging from biochemistry to chemical synthesis. In the present work, the energetics and solvent distributions for NH3+MeCl and Pyr+MeBr reactions were investigated in explicit solvent (water, methanol, acetonitrile, benzene, cyclohexane) by means of reactive molecular dynamics simulations. For polar solvents (water, methanol, and acetonitrile) and benzene, strong to moderate catalytic effects for both reactions were found, whereas apolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 92 publications
0
11
0
Order By: Relevance
“…Reactive dynamics simulations can also been carried out in solution. MS-ARMD treatments have been applied to the Claisen rearrangement in solution and in chorismate and for two Menshutkin-type methyl transfer reactions in different solvents . Another example is the F + CD 3 CN abstraction reaction to form DF + CD 2 CN in CD 3 CN, which was treated with a multistate empirical valence bond (EVB) approach .…”
Section: Reaction Dynamicsmentioning
confidence: 79%
See 2 more Smart Citations
“…Reactive dynamics simulations can also been carried out in solution. MS-ARMD treatments have been applied to the Claisen rearrangement in solution and in chorismate and for two Menshutkin-type methyl transfer reactions in different solvents . Another example is the F + CD 3 CN abstraction reaction to form DF + CD 2 CN in CD 3 CN, which was treated with a multistate empirical valence bond (EVB) approach .…”
Section: Reaction Dynamicsmentioning
confidence: 79%
“…MS-ARMD treatments have been applied to the Claisen rearrangement in solution and in chorismate 149 and for two Menshutkin-type methyl transfer reactions in different solvents. 42 Another example is the F + CD 3 CN abstraction reaction to form DF + CD 2 CN in CD 3 CN, which was treated with a multistate empirical valence bond (EVB) approach. 150 This work reproduced the experimentally observed 151 solvatochromic shift of the DF product in CD 3 CN and reported that the DF product contains a significant amount of vibrational energy (v = 2−3).…”
Section: ■ Reaction Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…For one of the systems, Pyr + MeBr experimentally determined barrier heights for acetonitrile and hexane as the solvent were 22.5 kcal mol −1 and 27.6 kcal mol −1 which compare with 23.2 kcal mol −1 and 28.1 kcal mol −1 from MS-ARMD simulations. 221 …”
Section: Reaction Dynamicsmentioning
confidence: 99%
“…On the other hand, there is another group of solvent effects, termed specific solvent (or solvation) effects , which depend on solute-solvent interactions of the ion-dipole and acid-base types in mainly dipolar aprotic solvents ( Parker, 1962 ; Epley and Drago, 1967 ; Parker, 1969 ) which affect the rates and mechanisms of chemical reactions executed in them. Considerable work has been achieved in determining solvent effects in nucleophilic substitution and a great variety of other reactions ( Ritchie, et al, 1967 ; Abraham, 1986 ; Reichardt, 2007 ; Cainelli et al, 2009 ; Turan et al, 2022 ). The predictions of the effect of solvent change on such reactions have generally been borne out by published experimental results.…”
Section: Introductionmentioning
confidence: 99%